Alex Corason - Abnormal Heart Sounds (OSCE Case) - Ralitsa Akins (Association of American Medical Colleges, 2011)
Abstract Introduction This objective structured clinical examination (OSCE) case was created for use with standardized patients (SPs), for teaching and/or evaluation purposes. The case is intended for teaching/examination of medical students, years 1 through 4 (depending on medical school's type of curriculum), as well as residents and faculty development. Methods The case follows that of 61-year-old Alex Corason, who comes in for a scheduled annual physical exam. The resource file contains information necessary for training SPs, presented in a table format. It describes the case, and the way it was used/validated. It also contains SP training notes and additional details. A heart sounds simulator will be necessary to implement the case. The recommended length of the teaching session is 1 hour and 15 minutes. Results The case has been successfully implemented with students at the Paul L. Foster School of Medicine at Texas Tech University Health Sciences Center El Paso. Discussion The notion of training SPs in the context of a role, rather than for specific interrogative props is gaining momentum across the nation and is considered a possibility for SP training for the USMLE Step 2 CS examination.